PENGARUH PERKEMBANGAN KEPARIWISATAAN DAN SISTEM KEKERABATAN TERHADAP SISTEM BAGI HASIL USAHA TANI PADI SAWAH DI BALI - Ketut Budi Susrusa; Saptono Iqbali (PIRAMIDA, 2008)
High population growthled to a scarcity of arable land in Indonesia. During 1963-1993 periods, farmer households have increased 1.77% i.e, almost three times than the extend of agricultural land. Soe, the land that is held by the farmer households were not only decreased in its size, but also increased in its inequality. Furthermore, this phenomenon encouraged the existence of share cropping contract. Sharecropping contract is an old institution that was known since Babylonian era ( ± 2300 BC) and still showing controversial issues related to agricultural productivity. Certainly, the institution that was born in along history of mankind could not be easily change, however some modification should be conducted along with the implementation of recent agricultural debelopment programs. The objectives this study was identify the change of sharecropping contract on rice farming along with development of economy in Bali which was also stimulated by development of tourism and to learn weather or not sharecropping contract was contra productive in terms labor used and farming performance. This study was conducted at the subaks area, three within and three others of tourism area. The population was classified into three group, owner-cultivator, non-kinship-sharecrpper, kinship- sharecropper. Farming intensity was measured by the indicator of the used of labor and inputs, whereas farm performance will be evaluated by land productivity and farm income. This study reveals that the more developed economy within a region, the better sharecropper’ s bargaining position. Furthermore, kinship-sharecropping contract was as not bad as the general opinion that is not agreed to sharesropping contract. Labor utilization and farm performance both in kinship sharecropping were consistent with enforceable contract that is led to optimizing input allocation. From the view points of owners-sharecropping relationships it was indicated that the owners held control upon the allocation of farm inputs.